(untitled) (Academicia Globe: Inderscience Research, 2022)
The article is devoted to the role of ethno-religious tolerance relations of more than 130 nations and people living in the New Uzbekistan in ensuring interethnic harmony and the principles of religious tolerance in the Constitution and legislation of the Republic of Uzbekistan.